Сверхтонкие взаимодействия на ядре иона лантана в соединении LaMnO₃ - Агзамова, П.А.; Лескова, Ю.В.; Никифоров, А.Е.; Гончарь, Л.Э.; Попов, С.Э. (Физика низких температур, 2007)
The influence of orbital and magnetic structures on the hyperfine interaction between the nuclear magnetic moment of lanthanum ions and the magnetic subsystem of manganese ions in LaMnO3 is investigated. A temperature dependence of the nuclear magnetic resonance spectrum of the polycrystal in external magnetic field is consructed. It is shown that the anisotropic hyperfine interaction, caused by the lanthanum external p-shells polarization, plays a major role.This model makes it possible to describe adequately the experimental data.